Valence engineering of ionic molecular crystals: monovalent–divalent phase diagram for biferrocene–tetracyanoquinodimethane salts. Issue 11 (24th February 2017) - Mochida, Tomoyuki; Funasako, Yusuke; Akasaka, Takahiro; Uruichi, Mikio; Mori, Hatsumi
Abstract : Ionic molecular solids composed of biferrocene derivatives (D) and tetracyanoquinodimethane derivatives (A) produce either divalent salts ([D] 2+ [A2 ] 2− ) or monovalent salts ([D] + [A2 ] − ) depending on the redox potential and molecular volume of the components. Abstract : The valence state of ionic molecular solids composed of biferrocene derivatives (D) and tetracyanoquinodimethane (TCNQ) derivatives (A), either monovalent ([D] + [A2 ] − ) or divalent ([D] 2+ [A2 ] 2− ), can be controlled by changing the redox potentials and molecular volumes of the components.